Composite of manganese dioxide impregnated in porous hollow carbon spheres for flexible asymmetric solid‐state supercapacitors. (10th September 2019) - Wang, Xinyu; Ma, Liwen; Sun, Juncai
Summary: Compared with symmetric supercapacitors, asymmetric supercapacitors are been widely applied in energy storage devices because of delivering an impressible energy density. Herein, a simple temple strategy was used to fabricate the porous hollow carbon spheres (PHCS) with high specific surface area of 793 m 2 g −1, large pore volume of 1.0 cm 3 g −1 and pore size distribution from micropores to mesopores, serving as the capacitive electrodes of asymmetric supercapacitors. Subsequently, manganese dioxide (MnO2 ) was impregnated into the PHCS to form a faradic electrode with a promising performance, owing to a synergistic effect between high capacity MnO2 and conductive PHCS. Furthermore, the flexible asymmetric solid‐state devices were constructed with PHCS anode, PHCS@MnO2 cathode, and PVA/LiCl electrolyte, extending a voltage window up to 1.8 V. The extensive voltage window would lead to an increased energy density. In our case, the flexible asymmetric sandwich exhibit excellent electrochemical performance in terms of a high energy density capacity of 26.5 W·h kg −1 (900 W kg −1 ) and superior cycling performance (10 000 cycles). Therefore, the developed strategy provides a strategy to achieve the PHCS‐based composites for the application in the asymmetric solid‐state supercapacitors, which will enable a widely field of flexible energy storage devices. Abstract : Porous hollow carbon spheres (PHCS) and PHCS@MnO2 with large pore volume and high specific surface area were obtained and served as both cathodes and anodes of flexible asymmetric solid‐state supercapacitors. The resultant flexible asymmetric solid‐state supercapacitors exhibit a high energy/power density and stable electrochemical performance even at various bending states.